Hollow bean-pod-like SiO2-supported-SnO2/C nanocomposites for durable lithium and sodium storage. Issue 4 (5th January 2017) - Yang, Linyu; Li, Site; Liu, Jun; Zhu, Kunjie; Liu, Sailin; Lei, Ming
Abstract : A hollow bean-pod-like SiO2 -supported-SnO2 /C structure is designed for durable and stable lithium and sodium storage. Abstract : In order to better resolve the large volume expansion problem of SnO2 -based anode materials, a hollow bean-pod-like SiO2 -supported-SnO2 /C nanostructure with a sufficient internal void space is designed. Dual voids exist in this structure in combination with a SiO2 support in the core and carbon as an outside shell, providing triple guarantees to improve the performance of SnO2 -based anode materials for Li and Na storage. As a result, after 550 charge/discharge cycles, a discharge capacity of 649 mA h g −1 can still be obtained for Li storage, and a discharge capacity of 104 mA h g −1 can still be maintained after 1000 charge/discharge cycles for Na storage.